PENGATURAN PROSEDUR PEMBATALAN SERTIPIKAT HAK ATAS TANAH YANG MERUPAKAN BARANG MILIK NEGARA - Anak Agung Istri Diah Mahadewi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
AstractThis study discusses, "regulation of Procedure Cancellation of Certificate of Land whichis the State Owned Assets", which aims to study theoretically on Cancellation of Certificateof Rights to the land including State owned Assets, ie, how the implementation Regulation ofCancellation of Certificate of Land to include of State.This research is a law that is derived from primary and secondary legal materials werethen analyzed by using the approach of legislation and legal concepts and approaches usinganalytical tools and techniques argumetasi legal description.Discussion and research results can be summarized as follows: Regulation Procedurecancellation of Certificate of Land which is the State Owned Assets can not provide legalcertainty for the National Land Agency officials in conducting cancellation, because to thestate owned assets known as asset removal must be approved by Property Manager theMinister of Finance, while the state owned assets such as land has issued a certificate if theobject of the dispute and has permanent legal force in terms of the form of action settlementwith the cancellation of the certificate of land Rights. So in this case the absence of a definiteregulation that can be used as guidelines for the Government Apparatus to take legal action inthe form of cancellation of Certificate of Land Rights